Is there such a thing as a "natural" disaster? - Lassa, Jonatan A. (2016)
Being vulnerable to the forces of nature is entirely social and political economic decisions. This article provides an overview of 40 years of critical disaster studies and why critical approach to understanding disasters can save lives.